Annual president's dinner - Estrada, Ariston (Animo Repository, 1961)
Five faculty members received special awards for their contributions to the work of the Christian Brothers, at the annual President's dinner. The awardees for the College were: Ariston Estrada, Provost Waldo Perfecto, Academic Prefect Gerardo Cinco, Administrative officer Carlos Valdez, Executive Officer and Rogelio Lao, Athletics Director.